Performing Theater under the Dictatorship: Strategies, Accommodations, and Dissent in Santa Fe, Argentina - Alonso, Luciano (Hispania Nova, 2026)
A growing body of recent research demonstrates that theatrical productions and performances were not only subject to repression and subject to censorship during Argentina’s last military dictatorship, but also served as spaces for the expression of dissent. In the case of the city of Santa Fe and its conurbation, it is possible to appreciate how individual and collective actors in the theatrical field navigated a constant interplay of restrictions and authorizations with local and provincial authorities. Building on the approaches undertaken in previous works, this paper aims to study the strategies followed by some members of the Santa Fe cultural space in the face of public policies and offer conceptualizations that allow for their understanding.